Periodontal disease and sports performance: a systematic review and meta-analysis - Ferreira, R. O.; Frazão, D. R.; Martins Ferreira, M. K.; Baraúna Magno, M.; Fernandes Fagundes, N. C.; Kuchenbecker Rosing, C.; Cople Maia, L.; Lima, R. R. (Research in Sports Medicine, 2024)
This systematic review and meta-analysis aimed to assess the association between athletic performance and periodontal disease (PD). Observational studies published up to April 2022 were searched in online databases (PubMed, Scopus, Web of Science, The Cochrane Library, LILACS, OpenGrey, and Google Scholar). PECO statement focused on studies with professional athletes (Participants) with PD (Exposition) compared to those with healthy periodontium (Comparison) and its effects on sports performance (outcome). Searches were conducted according to the PRISMA guidelines (registration protocol: 10.17605/OSF.IO/7ADH6) and risk of bias evaluation according to the Joanna Briggs Institute checklist. A total of 793 references were retrieved, of which eight were considered eligible. Two studies did not show an association between clinical PD parameters and performance. A meta-analysis with 396 participants suggested a relationship between PD and self-reported reduction in sports performance (odds ratio [OR] = 1.55; 95% confidence interval [CI] 1.04-2.31; p = 0.03; I2 = 0%) with moderate quality of evidence accordingly GRADE analysis. Despite the differences in performance evaluations between studies, PD was associated with reduced self-reported sports performance. Additional studies assessing confounding factors and objective assessment of PD and performance are needed to clarify the real effect of both conditions.